Importance of grassy and forest non-crop habitat islands for overwintering of ground-dwelling arthropods in agricultural landscapes: A multi-taxa approach. (November 2022) - Knapp, Michal; Štrobl, Martin; Venturo, Alfredo; Seidl, Miroslav; Jakubíková, Lada; Tajovský, Karel; Kadlec, Tomáš; González, Ezequiel
Abstract: Non-crop habitats are supposed to provide valuable resources to beneficial arthropods inhabiting agricultural landscapes during both the growing and winter seasons. Unfortunately, studies focused on the performance of non-crop habitats during the winter period are much less abundant, despite their importance for efficient biodiversity conservation measures. In this study, we assessed the distribution of ground-dwelling arthropods overwintering on arable land as well as the boundaries and interiors of neighbouring grassy and forest non-crop habitat islands. Myriapods, spiders, carabid and rove beetles were collected using a combination of quadrat sampling (soil sampling) and pitfall trapping. Our results revealed the importance of both non-crop habitat islands for overwintering arthropods, though slightly higher abundance and species richness were recorded in forest compared to grassy islands. Abundance and species richness of overwintering arthropods were lower on arable land for all the investigated taxa. Carabid and rove beetles overwintered more on non-crop boundaries than interiors, whereas spiders and myriapods used both boundaries and interiors. Landscape composition had stronger effects on carabids and myriapods collected with pitfall traps, which were benefitted in landscapes with high non-crop habitat cover. Grassy and forest non-crop habitat islands hosted different assemblages of myriapods, carabids and rove beetles, highlighting the complementarity of both non-crop habitat types for ground-dwelling arthropods. We recommend to preserve all existing non-crop habitat patches and to create new permanent non-crop habitat patches in intensively managed agricultural landscapes, as even relatively small non-crop habitat islands within the cultivated land can play a relevant role for overwintering arthropods. Highlights: Extremely low winter abundances of arthropods were recorded directly on arable land. Carabid and rove beetle abundance and diversity were highest in habitat boundaries. Both grassy and forest non-crop habitats were important for arthropod overwintering. Most groups had different species composition in grassy and forest islands. We recommend preserving all existing non-crop habitats islands and creating new ones.